Balancing the self Medicine, politics and the regulation of health in the twentieth century - Jackson, Mark; Moore, Martin D. (Manchester University Press, 2020)
Concepts of 'balance' have been central to modern politics, medicine and society. Yet, while many health, environmental and social challenges are discussed globally in terms of imbalances in biological, social and ecological systems, strategies for addressing modern excesses and deficiencies have focused almost exclusively on the agency of the individual. Balancing the Self explores the diverse ways in which balanced and unbalanced selfhoods have been subject to construction, intervention and challenge across the long twentieth century. Through original chapters on subjects as varied as obesity control, fatigue and the regulation of work, and the physiology of exploration in extreme conditions, the volume analyses how concepts of balance and rhetorics of empowerment and responsibility have historically been used for a variety of purposes, by a diversity of political and social agencies. Historicising present-day concerns, as well as uncovering the previously hidden interests of the past, this volume's wide-ranging discussions of health governance, subjectivity and balance will be of interest to historians of medicine, sociologists, social policy analysts, and social and political historians alike.